THE STRUCTURE AND CONTENT OF TEACHING HIGH SCHOOL STUDENTS AL-FARABI TRIGONOMETRY, FOCUSED ON THE DEVELOPMENT OF THEIR COMPUTATIONAL THINKING - Akzholova А.A.; Kamalova, G.B.; Kuttykozhaeva, Sh.N. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
The trigonometric heritage of al-Farabi, the great thinker of the Middle Ages, who made an invaluable contribution to the development of world science and civilization, is of enormous theoretical and practical value. It offers unique algorithms for finding the sin 1 degrees and constructing trigonometric tables necessary for solving various practice problems. Their inclusion in modern computer and mathematical education will not only popularize the legacy of the great scientist, but will also enrich the content of teaching trigonometry, strengthening its applied orientation, expand the system of subject knowledge of students, and contribute to the development of skills that determine the essence of computational thinking, which is one of the important goals of modern education. Al-Farabi’s trigonometry training should be focused on achieving the specified results. Adequate to the goals and objectives of teaching al-Farabi trigonometry to schoolchildren, it is advisable to determine its subject-thematic content. Purpose of the study: to determine the structure and content of teaching al-Farabi trigonometry, aimed at developing students’ computational thinking skills. Results: the basic principles and methods for selecting content are determined, on the basis of which a model of the concept system is built, the structure and content of teaching al-Farabi trigonometry in the context of education digitalization focused on the development of students’ computational thinking are determined.